TECHNOLOGICAL GAP IN KHARIF SORGHUM (Sorghum bicolor L.) PRODUCTION TECHNOLOGIES IN MARATHWADA REGION - PAWAR, G.S., GHUGE, S.N, KADAM, R.P and (The Journal of Research, PJTSAU, 2017)
The study was conducted in purposively selected three talukas viz., Kandhar, Mukhed and Loha of Nanded District of Marathawada region of Maharashtra state during the year 2014-15. From each taluka, four villages selected purposively and from each village 10 respondents were selected randomly, there by constituting a total sample size of 120 respondents. It was revealed that 67.50 per cent of farmers had medium technological gap followed by 18.33 per cent and 14.17 per cent had low and high technological gap in kharif sorghum production technology, respectively. Whereas practice wise technology gap among various recommended technologies, there was high technological gap in plant protection 88.64 per cent followed by intercultural operation 76.25 per cent, seed treatment 74.30 per cent, use of FYM 65.93 per cent and weed management 62.18 per cent.